Relation of Type 1 Diabetes Mellitus with Familial Hypercholesterolemia in Children; A Review Study - Ahmed Namaan Sheikh, Syed Aqeel Haider, Muhammad Amir Saeed Butt, Abdul Aleem Samoon, Shehla Naseem, Muhammad Zaman Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Type 1 diabetes mellitus (T1DM) and familial hypercholesterolemia (FH) are two different genetic disorders with serious health consequences. T1DM is an immune mediated disease that impacts the pancreas and causes a lack of insulin levels, whereas FH is an inherited condition that causes high cholesterol levels in the blood. FH and type 1 diabetes mellitus are both linked to substantial morbidity and premature mortality due to atherosclerotic cardiovascular disease. Material and Methods: To better understand the ongoing debate regarding the relationship of type 1 Diabetes mellitus with familial hypercholesterolemia. Medline search of the literature was held between 2016 and 2022. From this search, 35 articles with relevant material were selected. Results: The data from the previous conbined studies show that there is a link between types 1 dm with familial hypercholesterolemia in children. Less physical activity, higher BMI value and obesity are some of the areas that link hypercholesterolemia with diabetes mellitus 1. Therefore, it is advised to have metabolic control to treat hyperlipidemia. Conclusion: Familial hypercholesterolemia is significantly linked with type 1 diabetes mellitus and is more common among children and adolescents. Dyslipidemia is more frequently reported among female patients. The most of the patients of dyslipidemia shows elevated LDL-C and low HDL-C. Keywords: Type 1 diabetes mellitus, familial hypercholesterolemia, low-density lipoprotein, blood glucose level and cardiovascular disease.